Identification of groundnut germplasm resistant to tikka disease in Gujarat: IDENTIFICATION OF GROUNDNUT GERMPLASM RESISTANT TO TIKKA DISEASE - A VIJAYA BHASKAR; A M PARAKHIA; A F AKBARI; S V PATEL (Journal of Oilseeds Research, 2013)
Early and late leaf spots, caused by Cercospora arachidicola and Phaeoisariopsis personata, respectively are serious diseases of groundnut in Saurashtra region of Gujarat State. A total of 164 germplasms were screened along with susceptible check (GG-2) against both the diseases under natural epiphytotic conditions in kharif season to select resistant sources. The germplasms were scored using 1-9 scale at 90 days after sowing. The results indicate that no germplasm wasimmune or highly resistant to both the leafspots. Thirty six entriesshowed resistant reaction to the diseases.